2020
DOI: 10.1007/s11606-020-06009-4
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Notification Calls Prior to Mailed Fecal Immunochemical Test in Previously Screened Patients: a Randomized Controlled Trial

Abstract: BACKGROUND: Phone calls as part of multimodal fecal immunochemical test (FIT) outreach are effective but resource-intensive. Previous studies of advanced notification calls before FIT mailing have not differentiated patients' prior screening status. OBJECTIVE: To determine the effectiveness of a phone call preceding mailing of a FIT kit on test completion rate for patients who have completed a prior FIT. DESIGN: Randomized controlled trial nested within a larger study. All patients were assigned to receive org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The key characteristics of the 32 included articles are summarised in Table 1 9,11–13,15,18,24,29,30,33–55 . Of these, the majority originated in the United States of America (41%), with others from the United Kingdom (25%), Australia (13%), Denmark (3%), Italy (3%), Latvia (3%), the Netherlands (3%), New Zealand (3%), Spain (3%), and Sweden (3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key characteristics of the 32 included articles are summarised in Table 1 9,11–13,15,18,24,29,30,33–55 . Of these, the majority originated in the United States of America (41%), with others from the United Kingdom (25%), Australia (13%), Denmark (3%), Italy (3%), Latvia (3%), the Netherlands (3%), New Zealand (3%), Spain (3%), and Sweden (3%).…”
Section: Resultsmentioning
confidence: 99%
“…The invitation process was described, including when to expect the screening offer, what to do upon its arrival, and in the case of one mailed notification, how to distinguish the screening invitation from other mail, 18 presumably to prevent misplacement. Details of what to expect during the screening procedure, for example, a description of how to complete the bowel cancer screening kit 24,51,54 or how a cervical screening test is performed, 42 as well as what to expect after the test, such as the outcomes of a positive test result, 38,50,54 were also sometimes provided. Advance notifications commonly provided facts about where to access more information about screening, usually providing helplines, websites, and other printed materials for reference, or in the case of phone calls, the opportunity to seek answers directly from the caller 34,50,51 …”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were published between 2021 and 2022; 14 studies investigated interventions in the United States; and the most common study designs used were randomized controlled trials and controlled clinical trials (n = 14). Most studies (n = 17) described the included populations as having no or limited access to the healthcare system (e.g., immigrant populations [ 52 ], uninsured groups [ 38 40 ], and publicly funded safety-net health system in United States [ 42 , 43 ]). Only five studies stratified findings for the population group with no regular healthcare providers.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies on FIT effectiveness had FIT kits returned by mail (n = 12). In the quality appraisal, 16 studies scored as weak [ 31 , 33 , 37 , 38 , 40 42 , 44 49 , 51 , 52 , 54 ]; eight scored as ‘moderate’ [ 30 , 32 , 34 , 36 , 39 , 43 , 50 , 53 ]; and one [ 35 ] as ‘strong’. Overall, the quality of evidence was weak due to parameters related to selection bias, study design, and reporting of follow-up rates.…”
Section: Resultsmentioning
confidence: 99%
“…in the usual care group) [42]. Other study that included only population with a history of FIT completion found modest differences in FIT completion between the group receiving noti cation phone calls and the group with no phone calls [43]. This suggests that groups with prior history of FIT may require less reminder methods for the subsequent FIT completion [43].…”
Section: Methods Of Delivery For Fit: Mail-out and In-personmentioning
confidence: 99%